2010
DOI: 10.1152/ajpregu.00599.2009
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a spinal, urine storage reflex, inhibitory center and its regulation by 5-HT1A receptors in female cats

Abstract: Urine storage is facilitated by somatic (pudendal nerve) and sympathetic [hypogastric nerve (HgN)] reflexes to the urethral rhabdosphincter (URS) and urethral smooth muscle, respectively, initiated by primary afferent fibers in the pelvic nerve (PelN). Inhibition of storage reflexes is required for normal voiding. This study characterizes a urine storage reflex inhibitory network that can be activated by PelN afferent fibers concurrently with the reflexes themselves. Electrical stimulation of PelN produced evo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 27 publications
1
29
0
Order By: Relevance
“…However, central 5-HT 1A function in bladder and sphincter activity is still unclear because its role appears to be strongly species dependent. In cats, 5-HT 1A activation results in inhibition of parasympathetic excitatory input to the urinary bladder and facilitation of the external urethral sphincter (EUS) EMG activity [53,54].…”
Section: Source Of 5-ht In Urinary Bladdermentioning
confidence: 99%
See 1 more Smart Citation
“…However, central 5-HT 1A function in bladder and sphincter activity is still unclear because its role appears to be strongly species dependent. In cats, 5-HT 1A activation results in inhibition of parasympathetic excitatory input to the urinary bladder and facilitation of the external urethral sphincter (EUS) EMG activity [53,54].…”
Section: Source Of 5-ht In Urinary Bladdermentioning
confidence: 99%
“…The increase in sphincter activity by 5-HT 1A is achieved by a process of disinhibition: the spinal, urine storage reflex, inhibitory center (SUSRIC) inhibits the urethral sphincter motor nucleus, and SUSRIC activity is inhibited by supraspinal 5-HT 1A receptors [53]. In contrast to that in cats, central 5-HT 1A activation in rats causes enhancement of reflex activity in the bladder and sphincter, whereas its blockade reduces these reflex activities [55,56].…”
Section: Source Of 5-ht In Urinary Bladdermentioning
confidence: 99%
“…Importantly, the observed inhibition was still observed after acute spinal cord transection at T10 confirming the spinal cord location of the inhibitory center, which the authors have termed a spinal, urine storage reflex, inhibitory center (SUSRIC). As detailed in the paper (14), additional data from the study suggest two separate SUSRICs, one being involved in the sympathetic storage reflex and a separate one being involved in the somatic urine storage reflex. Under normal conditions, the authors suggest that a SUSRIC may function as a redundant or additional system to promote urethral relaxation (14).…”
Section: Micturition Reflexmentioning
confidence: 66%
“…Electrical stimulation of pelvic nerves elicited evoked potentials in electromyogram electrodes placed in the urethral sphincter/rhabdosphincter or in hypogastric nerve electrodes in anesthetized cats. Using a conditioning test paired-pulse paradigm, Karicheti et al (14) observed that the reflexes evoked by the second stimulus were inhibited. Importantly, the observed inhibition was still observed after acute spinal cord transection at T10 confirming the spinal cord location of the inhibitory center, which the authors have termed a spinal, urine storage reflex, inhibitory center (SUSRIC).…”
Section: Micturition Reflexmentioning
confidence: 99%
“…That it is also apparent in SCT cats adds this species to the list of those that possess a spinal PFPAPG. Whether this neural oscillator is related to the recently described "spinal, urine storage reflex, inhibitory center" in the cat [37] is not currently known.…”
Section: Detrusor-urethra Coordination In Nonhuman Mammalsmentioning
confidence: 99%